(untitled) (Studia austriaca, 2012)
Thomas Bernhard reflects in his posthumously published story collection Meine Preise the most important of his many literary awards, which were often associated with public scandals. This essay examines the mechanisms of authorship and self-stylization in the stories concerning the prizes received, shows the conglomeration of reality and fiction which characterizes his late work and offers a compact, interpretative survey of Bernhard’s prose volume in the light of his career in the literary field.